Clinical reproducibility of a low cost electronic apex locator - Nathalia Vilaça Soares; Emmanuel João Nogueira Leal da Silva; Claudio Malizzia Alves Ferreira; Renato Liess Krebs; Tauby de Souza Coutinho-Filho (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the clinical reproducibility of three electronic apex locators (EALs), Joypex 5, RomiApex A-15 and Novapex. Methods: Twenty-five patients requiring endodontic treatment were selected. Sixty root canals were measured by the three EALs to determine their respective working length, which was defined as a zero reading on the EAL. A new K-file of the same size was used for each measurement. The file length was fixed with a rubber stop and measured with a caliper to an accuracy of 0.1 mm. Data were analyzed statistically using paired t-tests with the Bonferroni correction and Bland-Altman plot to determine the reproducibility of clinical data among the EALs. Significance level was set at 5%. Results: Mean and standard deviation values measured by the three EALs showed no statistically significant differences. Identical readings by all three EALs were found in 38% of root canals. Fifty percent differed by less than ± 1.0 mm and only 1.3% exceeded a difference of 2.0 mm. Conclusions: The clinical reproducibility of the three devices was confirmed with no significant differences among them, indicating that they are effective for clinical use.